Seabiscuit the screenplay - Ross, Gary 1956-; Hillenbrand, Laura
Seabiscuit, the #1 New York Times bestseller, became one of this year's most popular and critically acclaimed movies. Now, here is the complete shooting script of this extraordinary film from Universal Pictures, Dreamworks Pictures, and Spyglass Entertainment, featuring a foreword from Seabiscuit author Laura Hillenbrand and twenty-four full-color still photos from the motion picture. An American epic of triumph and perseverance set during the Great Depression, this stunning adaptation brilliantly dramatizes the story of the three men and the down-and-out racehorse that took them and the entire nation on the ride of a lifetime.